Analisis Kebijakan, Sarana Prasarana dan Sumber Daya Manusia Dalam Persiapan Re-Akreditasi - Riri Julianti; Sumengen Sutomo; Aldiga Rienarti Abidin; Jasrida Yunita; Reno Renaldi (Jurnal Kesehatan Komunitas, 2021)
Accreditation is an acknowledgment of the public health center agency, by an independent accreditation agency set by the Minister of Health after meeting the first level health facility service standards to improve the quality of services on an ongoing basis. Puskesmas Bagansiapapi is a middle-accredited puskesmas that will go through a re-accreditation process scheduled for 2020 and is planned to be a pilot health center in Rokan Hilir district. Based on the results of initial interview with Head and Staff of Public Health center, there are some recommendations from surveyors for 2020’s re-accreditation preparation such as policies, infrastructure and human resources. Downstream 2020.This type of research is qualitative descriptive exploratory research with in-depth interviews, observation and document review with the respondents of the quality head, an admin’s leader, an UKM’s Leader, the head of UKP, the Head of Public Health Center and the Internal Health Staff. The results showed that the preparatory policies for accreditation had been implemented well. The facilities and infrastructure in preparation for accreditation have not met Permenkes 43 of 2019 and have not met the needs of the community. Judging from the adequacy of human resources has not met the standard Permenkes No. 43 of 2019 in the form of environmental sanitation workers, health information system personnel, financial administration staff, administrative staff and those needed by medical record health centers and information technology workers.Preparation for Puskesmas Bagansiapiapi accreditation in policy has been well implemented, infrastructure and human resources do not meet standards.